Pengembangan Kit Praktikum Quincke Untuk Meningkatkan Hasil Belajar Peserta Didik SMA Pada Materi Gelombang Bunyi - Marsya, Zafirah Dini; Sucahyo, Imam (IPF: Inovasi Pendidikan Fisika, 2023)
Abstract This study aims to describe the development process and the feasibility of the Quincke practicum kit which was developed to improve the learning outcomes of high school students on sound waves. This type of research uses the ADDIE stage research method (Analysis, Design, Develop, Implementation, Evaluation) with nonprobability sampling using purposive sampling. The trial design was a pre-experimental design, namely one group pre-test post-test. The research targets were 34 XI IPA 2 students at SMAN 12 Surabaya. The results of the research show that the development of this media refers to the Analyze, Design, Development, Implementation, and Evaluation (ADDIE) stage. The analysis stage by analyzing the basic problems faced in schools, identifying the resources needed by students, selecting the media to be developed through pre-research with teacher interviews, student questionnaires, and direct observation; The design stage is by designing the initial Quincke practicum kit that will be developed as well as the learning tools; The development stage is by compiling the Quincke practicum media kit according to the needs of students; The implementation stage is by working on the pre-test questions, then testing the Quincke practicum kit, then working on the post-test questions; The development of the Quincke practicum kit media is suitable for use to improve the learning outcomes of class XI IPA 2 SMA students at SMAN 12 Surabaya as a physics learning medium in sound wave material, because it has fulfilled three aspects, namely the validity aspect of 87.5% which has been validated by three lecturers expert; practicality through observation of implementation of 92.5% of student response questionnaires of 94.5%; and the effectiveness obtained is 84% ??in terms of student learning outcomes. Keywords: ADDIE, Feasibility, Sound Waves, Quincke.